The Standard-Based Creative Arts Curriculum Implementation in Primary Schools: Teacher Perceptions, Agency, and Resource Availability - Alhassan, Hamza; Essel, Harry Barton; Kquofi, Steve (CV Sinergi Ilmu dan Publikasi, 2025)
This study examines the impact of teacher agency on the implementation of Ghana’s 2019 Standards-Based Creative Arts Curriculum in public and private primary schools. While the curriculum promotes creativity, cultural identity, and critical thinking, its implementation faces challenges such as inadequate resources, limited teacher training, and institutional neglect. Guided by the Concerns-Based Adoption Model (CBAM), the study investigates how teacher perceptions, professional autonomy, and resource environments affect curriculum enactment. A quantitative approach using a descriptive survey design was adopted, with data collected from 387 teachers (96.75% response rate). Structured questionnaires assessed teacher perceptions, instructional autonomy, and resource access. Statistical analysis revealed a mixed picture of teacher empowerment—high autonomy in instruction but limited involvement in decision-making. Resource constraints were a significant barrier, particularly in under-resourced public schools. Despite these limitations, teachers employed adaptive strategies to deliver Creative Arts instruction. The findings offer actionable insights for policymakers, teacher educators, and curriculum developers to strengthen implementation through improved resourcing and teacher support. By centering teacher perspectives, this study highlights the gap between curriculum design and classroom realities, advocating for creative arts as a vital component of holistic education in Ghana and across Africa.